SWOT Analysis of Sikeling Burger Business Development Strategy Using the Business Model Canvas Approach - Harahap, Muhammad Farhan; Nawawi, Zuhrinal M; Syahbudi, Muhammad (Universitas Alma Ata, 2024)
Business Model Canvas (BMC) is a strategic management framework developed by Alexander Ostewalder, a Swiss business theorist and author. It provides a visual representation of the business model, enabling easy understanding and analysis of the key elements that drive the business. Micro Business is the smallest type of business within Micro, Small, and Medium Enterprises. This research aims to find out how the business model is carried out at the Sikeling Burger business in the city of Medan using SWOT Analysis and transformed into a Business Model Canvas. This research approach uses qualitative research. The results of the SWOT analysis on the IFAS matrix have a score of 2.062 and EFAS has a score of 2.025 which shows that Quadrant I produces an Aggressive Strategy that supports aggressive growth policies by utilizing all strengths to seize maximum opportunities. These results become the basis for the Business Model Canvas where development strategies are carried out in all blocks, namely maintaining customer segmentation as a source of income and increasing the value proposition such as maintaining products and consumer relationships as well as using social media for promotions to get a revenue stream from selling burgers and other items.